Intragenic recombination generated two distinct Cf genes that mediate AVR9 recognition in the natural population of Lycopersicon pimpinellifolium - Van der Hoorn, Renier A. L. (The National Academy of Sciences, 2001)
Resistance gene Cf-9 of cultivated tomato (Lycopersicon esculentum) confers recognition of the AVR9 elicitor protein of the fungal pathogen Cladosporium fulvum. The Cf-9 locus, containing Cf-9 and four homologs (Hcr9s), originates from Lycopersicon pimpinellifolium (Lp). We examined naturally occurring polymorphism in Hcr9s that confer AVR9 recognition in the Lp population. AVR9 recognition occurs frequently throughout this population. In addition to Cf-9, we discovered a second gene in Lp, designated 9DC, which also confers AVR9 recognition. Compared with Cf-9, 9DC is more polymorphic, occurs more frequently, and is more widely spread throughout the Lp population, suggesting that 9DC is older than Cf-9. The sequences of Cf-9 and 9DC suggest that Cf-9 evolved from 9DC by intragenic recombination between 9DC and another Hcr9. The fact that the 9DC and Cf-9 proteins differ in 61 aa residues, and both mediate recognition of AVR9, shows that in nature Hcr9 proteins with the same recognitional specificity can vary significantly.